Методология объектно-ориентированной комплексной оптимизации проточных частей мощных паровых турбин с учетом переменного режима работы - Бойко, Анатолий Владимирович; Усатый, Александр Павлович; Авдеева, Елена Петровна (НТУ "ХПИ", 2014)
Разработана методология оптимизации проточной части мощных паровых турбин с учетом режимов эксплуатации. Представлена новая сложная иерархическая структура оптимизационной задачи реализованной в САПР «Турбоагрегат», которая основана на принципах единого интегрированного информационного пространства, путем добавления новых объектов оптимизации. Для организации эффективного информационного обмена процесс оптимального проектирования реализован с использованием рекурсивного обхода уровней оптимизации.

The methods of the object-oriented complex optimization of the flow pass of powerful steam turbine taking into consideration the operation modes has been developed. New optimization objects have been included into the complicated hierarchical structure of the project, which opened more opportunities for the design and modernization of steam turbines. This allows for the high-accuracy estimation of the efficiency of the turbine unit on the whole, for optimal solutions at simultaneous consideration of the control system (valve system), control stage, surge chamber and the remaining flow pass (HPC, APC, LPC). The realization of new optimization levels in the single integrated information space CAD "Turbounit" (computer-aided design system) provided the opportunity for the design of the optimal structure of powerful steam turbine intended for the operation in the broad range of the variation of mode parameters. To organize the efficient information exchange the process of optimal design was realized using the recursive by pass of optimization levels. Using the methods of experiment design theory at each recursion level the appropriate formal macromodels of objective functions and functional limitations have been created.
Methodology of the object-oriented complex optimization of the flow passes of powerful steam turbines taking into consideration the variable operation mode
Keywords: оптимальное проектирование; режим работы; паровая турбина; single integrated information space; optimal design; operation mode; steam turbine